The Application of Videos to Teaching English for Business Communication: EFL Learners’ Perspectives = Ứng dụng video vào giảng dạy tiếng Anh giao tiếp thương mại: Quan điểm của người học - Duong, My Tham (Đại học Quốc gia Hà Nội, 2020)
The global trends in the 21st century language learning and teaching have promoted interpersonal communication. Recently, there has been a high demand for learning tools which increase learners’ motivation and participation with a focus on communicative competence. This paper aims to explore English majors’ attitudes towards the application of videos in the Business Communication (BC) course at a Vietnamese university. It also explores the students’ favorite learning activities employed during the course. There were 125 third-year English majors participating in the mix-methods research in which both quantitative and qualitative data were collected for an in-depth analysis through the employment of a questionnaire and semi-structured interviews. The findings showed that the participants held a positive attitude (i.e., cognition, emotion, and behavior) toward a video-based Business Communication (VBC) course. As for favourite learning activities, furthermore, collaborative learning activities (e.g., group discussion, role-play, and conversation) tended to be preferred over individual-focused ones (e.g., oral presentation and story-telling).